Quality of embryos transferred and progesterone levels are the most important predictors of live birth after fresh embryo transfer: a retrospective cohort study - Cai, Qianfang (Springer US, 2013)
PURPOSE: To identify the independent predictors of live birth following IVF, and to assess the role of cohort-specific parameters, including antral follicle count (AFC), the number of oocytes retrieved, the total number of embryos, and the total number of good-quality embryos, in fresh IVF cycles. METHODS: A retrospective cohort study of 2,525 infertile women undergoing IVF between 2002 and 2007. The hypothesis that the number and quality of embryos transferred capture the effects previously attributed to cohort-specific variables was examined using mediation analysis and spline analysis. Independent predictors were identified by a bootstrap algorithm. Multivariable logistic regression was performed and the proportion of explained variation was measured to compare the relative importance of transfer-specific vs. cohort-specific predictors. RESULTS: The number of good-quality embryos transferred and progesterone level on the day of hCG administration ranked as the two most important predictors of live birth. Prospects of pregnancy started to decrease after progesterone level exceeded 0.6 ng/ml. The achievement of live birth in a fresh IVF cycle is primarily determined by the number and quality of embryos transferred, rather than by embryo cohort-specific variables. CONCLUSIONS: The associations between cohort-specific variables and live birth in a fresh IVF cycle are completely mediated by the quality of embryos transferred. Progesterone level on the day of hCG administration is an independent predictor of pregnancy and merits further investigation.